Killer Cell Immunoglobulin-Like Receptor Genes Polymorphisms in Macedonian Patients with Haematological Malignancies - Petlichkovski, Aleksandar; Stojanoski, Zlate; Dragan Cibrev; Spiroski, Mirko (My University, 2013)
Aim: The aim of this study was to examine the gene frequencies of 16 KIR genes and pseudogenes (KIR2DL1, KIR2DL2, KIR2DL3, KIR2DL4, KIR2DL5, KIR3DL1, KIR3DL2, KIR3DL3, KIR2DS1, KIR2DS2, KIR2DS3, KIR2DS4, KIR2DS5, KIR3DS1, KIR2DP1, and KIR3DP1) and KIR genotypes in Macedonian patients with haematological malignancies, to compare them with the corresponding frequencies of healthy Macedonians and to analyse eventual association of specific genes or genotypes with the studied haematological diseases. Material and Methods: The study included 63 patients of which 40 had acute myeloblastic leukaemia (63.5%), 11 (17.5%) had chronic myeloid leukaemia, 8 (12.7%) acute lymphoblastic leukaemia, 2 (3.17%) non-Hodgkin Lymphoma, 1 (1.59%) aplastic anemia, and 1 (1.59%) chronic lymphocytic leukaemia. Results: Comparison of KIR gene frequencies between the 63 patients and healthy Macedonians reveals statistically significant difference for KIR3DL2 (F= 1 in the control group, and 0.95 in the patients group, p=0.001). Another statistically significant difference was observed for the frequency of Bx3 and Bx439 genotypes both found more often in patients group (P=0.017 and P= 0.009, respectively). Conclusion: Further analysis, involving larger series of patients and targeted at the ligands of the KIRs are needed in order to determine a certain KIR gene and/or genotype as either predisposing, or protecting factor for haematological malignancy in patients from Republic of Macedonia.
Keywords: KIR receptors; hematological malignancies